Graceful numbers - Kiran R. Bhutani; Alexander B. Levin (International Journal of Mathematics and Mathematical Sciences)
We construct a labeled graph D(n) that reflects the structure of divisors of a given natural number n. We define the concept of graceful numbers in terms of this associated graph and find the general form of such a number. As a consequence, we determine which graceful numbers are perfect.